Health-related quality of life in children and adults with respiratory allergy in Colombia : Prospective study (2012)
ABSTRACT: Background: Allergic diseases are very common, with the estimated cumulative prevalence in Colombia for asthma and allergic rhinitis being 22.7% and 31.3% respectively, and with a clear upward trend. A major social as well as economic impact associated with allergic disease has been described. Because in Colombia there are no studies that assess the Health-Related Quality of Life (HRQOL) in allergic respiratory diseases, our aim is to describe the HRQOL in subjects with respiratory allergy and its association with clinical control variables. Methods: A prospective descriptive study was conducted among 76 Colombian subjects with rhinitis and asthma/allergic rhinitis. In order to evaluate the HRQOL, the instruments Kidscreen27 and SF-36 were applied. The scores obtained in the HRQOL fields were correlated with the following clinical variables: peak expiratory flow (PEF) and peak nasal inspiratory flow (PNIF). Results: In children, the better HRQL domain is present in the school environment (55.9) and the worst in psychological well-being (39.9). For adults the worst HRQL was found in the emotional function domain (55.6) while the physical function (81.7) had the best. There were no statistical differences between groups of asthma/allergic rhinitis and allergic rhinitis. Subjects with allergic asthma showed a strong correlation between the mental health domain and PEF values (r = −0717, p = 0.046). Conclusion: Mental health is more affected than physical health in Colombian subjects with respiratory allergy. There was a strong correlation between the mental health domain and the values of PEF in patients with asthma/allergic rhinitis